Transforaminal Lumbar Interbody Fusion (TLIF) versus Oblique Lumbar Interbody Fusion (OLIF) in Interbody Fusion Technique for Degenerative Spondylolisthesis: A Systematic Review and Meta-Analysis - Chang, Min Cheol (Life (Basel), 2021)
Preoperative pathology requiring fusion surgery has a great impact on postoperative outcomes. However, the previous clinical and meta-analysis studies did not control for the pathology. In this systematic review, the authors aimed to compare oblique lumbar interbody fusion (OLIF) with transforaminal interbody fusion (TLIF) as an interbody fusion technique in lumbar fusion surgery for patients with degenerative spondylolisthesis (DS). We systematically searched for relevant articles in the available databases. Among the 3022 articles, three studies were identified and met the inclusion criteria. In terms of radiological outcome, the amount of disc height restoration was greater in the OLIF group than in the TLIF group, but there was no significant difference between the two surgical techniques (p = 0.18). In the clinical outcomes, the pain improvement was not significantly different between the two surgical techniques. In terms of surgical outcomes, OLIF resulted in a shorter length of hospital stay and less blood loss than TLIF (p < 0.0001 and p = 0.02, respectively). The present meta-analysis indicated no significant difference in clinical, radiological outcomes, and surgical time between TLIF and OLIF for DS, but the lengths of hospital stay and blood loss were better in OLIF than TLIF. Though encouraging, these findings were based on low-quality evidence from a small number of retrospective studies that are prone to bias.